التمسك بالبطلان امام جهات القضاء الجزائي وكيفية الفصل فيه - صيـد عبد الله - جعنيط براهيم الخليل (جامعة المسيلة, 2024)
البطالن وصف يلحق العمل اإلجرائي الذي ال يتوفر فيه أحد العناصر الجوهرية التي يستلزمها القانون، ويكون في صورة جزاء اجرائي يترتب عليه عدم انتاج العمل المعيب ألثاره القانونية التي ترتبها القاعدة االجرائية المنظمة له فيما لو اتخذ بصورة صحيحة، وتأسيساً على ذلك يتحقق بطالن العمل االجرائي إذا تخلف أحد االجراءات الشكلية او الموضوعية الالزمة لصحته او بسبب اتخاذها بصورة معيبة وتهدف دراسة البطالن الى بيان القيمة العملية للقواعد الموضوعية والشكلية التي تحكم سير الخصومة الجزائية، اذ ان بطالن العمل االجرائي ال يترت ب بصو رة آلية لمجرد توافر المخالفة االجرائية وانما يبقى العمل الباطل بمثابة عمل صحيح منتج لكافة آثاره الى ان يتقرر بطالنه بحكم قضائي صادر عن المحكمة المختصة أياً كان نوع البطالن الذي يشوبه )مطلق أو َن الفرق بين نوعي البطالن يتمثل في أن البطالن المطلق ي نسبي(غير أ مكن للمحكمة ان تثيره من تلقاء نفسها ،عكس البطالن النسبي الذي ال يمكن تقريره اال اذا تمسك به صاحب المصلحة في تقريره. وألجل معالجة موضوع البحث اقتضى االمر اعتماد المنهج الوصفي بغرض دراسة طبيعة البطالن كما هي في الواقع، ووصفه وتبيان خصائصه باالعتماد على المصادر والمراجع القانونية، والمنهج التحليلي بهدف تحليل وتفسير النصوص القانونية المتعلقة بالبطالن كجزاء اجرائي ان تقرير البطالن يترتب عليه نوعين من االثار أولها اثار سلبية ترتبط بالعمل نفسه واالجراءات السابقة او الالحقة له بحيث يعجز العمل االجرائي عن إنتاج آثاره القانونية التي كان سيولدها لو نشأ صحيحا،ً كما ان البطالن قد يسري الى االجراءات الالحقة له اذا توافر َّن بطالن العمل االجرائي َ بينهما نوع من االرتباط يبرر ذلك التأثير بينهما، و فضالً عن ذلك فأ يؤدي الى اهدار الدليل المحصل عليه من العمل الباطل ، اال ان النظام االجرائي وضرورة االقتصاد في الوقت واالجراءات تقتضي عدم االفراط في التطبيق ألثار البطالن فال يتم التوسع فيه او التضييق من نطاقه على نحو يضيع الغرض المقصود منه، لذلك اجازت التشريعات االجرائية تصحيح البطالن في حاالت معينة و بوسائل محددة. وأخ يرا ينبغي توسيع البطالن كجزاء اجرائي باعتباره من أهم الضمانات في الخصومة الجزائية، بإثراء الحاالت التي استقر عليها القضاء، واالستفادة من بعض التشريعات التي نظمت نظرية البطالن، الكلمات المفتاحية: العمل االجرائي، الجزاء االجرائي، البطالن االجرائي، البطالن المطلق، البطالن النسبي، التمسك بالبطالن، أثار البطالن 167 Abstract Invalidity is a description attached to the procedural work that does not include one of the essential elements required by the law, and it is in the form of a procedural penalty that results in the defective work not producing its legal effects, which are therefore required by the procedural rule regulating it if it were to take a correct form and based on that, and the procedural work becomes invalid if it is not The numerical or objective unit necessary for its validity or because it takes a defective form. The study of invalidity aims to demonstrate the practical value of the objective and formal rules that govern the conduct of the criminal dispute, as the invalidity of a procedural action does not result automatically merely because of the presence of a procedural violation. Rather, the invalid action remains a valid action that produces all its effects until its invalidity is determined by a judicial ruling issued by the competent court, whatever The type of invalidity involved was (absolute or relative), but the difference between the two types of invalidity is that the court can raise it on its own initiative, unlike relative invalidity, which can be decided only if the interested party adheres to it in his decision. In order to address the subject of the research in the best way, it was necessary to adopt the descriptive approach for the purpose of studying the nature of invalidation as it exists in reality, describing it and clarifying its characteristics, relying on legal sources and references, and the analytical approach with the aim of analyzing and interpreting the legal texts related to invalidation as a procedural penalty. Determining invalidity results in two types of effects, the first of which is negative effects related to the work itself and the procedures preceding or following it, such that the procedural work is unable to produce the legal effects that it would have generated if it had arisen correctly. In addition, invalidity may apply to subsequent procedures if there is some kind of connection between them that justifies that effect. In addition, the invalidation of the procedural work leads to the wasting of the evidence obtained from the invalid work. However, the procedural system and the necessity of saving time and procedures require not over-applying the effects of the invalidation, so it should not be expanded or narrowed in its scope in a way that would lose its intended purpose. Therefore, Procedural legislation permits the correction of invalidity in specific cases and by specific means Finally, invalidation should be expanded as a procedural penalty, as it is one of the most important guarantees in criminal litigation, by enriching the cases the judiciary has settled on, and benefiting from some of the legislation that regulated the theory of invalidity.
Keywords: العمل االجرائي، الجزاء االجرائي، البطالن االجرائي، البطالن المطلق، البطالن النسبي، التمسك; بالبطالن، أثار البطالن